Validity of the Medication Adherence Rating Scale for Adherence to Inhaled Corticosteroids among Older Adults with Asthma or Chronic Obstructive Pulmonary Disease. (2nd January 2020) - Tangirala, Neelima C.; O'Conor, Rachel; Wolf, Michael S.; Wisnivesky, Juan P.; Federman, Alex D.
Abstract: Regular use of inhaled corticosteroids (ICS) is the standard of care for patients with persistent asthma and chronic obstructive pulmonary disease (COPD). Adherence to ICS is measured using the 10-item Medication Adherence Report Scale (MARS), a self-reported medication adherence assessment. However, data on the validity of this measure are limited. Data were obtained from two cohort studies that examined the association of health literacy with self-management behaviors among adults ages 65 and older with asthma and adults ages 40 and older with COPD. ICS adherence was objectively measured over a 4-week period using electronic monitoring devices. Adequate adherence by MARS assessment was defined as a score ≥4.5, and by electronic monitoring as ≥80% of doses prescribed. We assessed the criterion validity using correlations between self-reported adherence and electronic adherence. Receiver Operating Characteristic (ROC) curve analysis was performed between the two measures. Among patients with asthma, the continuous values for adherence measured by self-report and electronically were weakly correlated ( r = 0.33, p < 0.001); similarly, the agreement between the dichotomized measures was weak (kappa 0.30, p =.49). Findings were similar for COPD patients: r = 0.26, p = 0.003; kappa 0.19, p = .60. Area under curve (AUC) values generated from ROC analysis was 0.69 and 0.61, for asthma and COPD patients, respectively. Commonly used measure for adherence performed weakly compared to electronic monitoring in separate populations of patients with asthma and COPD. Investigators measuring self-reported medication adherence among patients with these pulmonary diseases should consider using alternative instruments or using objective measures exclusively.